Correlates of sports practice, occupational and leisure-time physical activity in Brazilian adolescents - Silva, Danilo R P; Fernandes, Rômulo A. [UNESP]; Ohara, David; Collings, Paul J.; Souza, Mariana F.; Tomeleri, Crisieli M.; Ronque, Enio R. V.; Sardinha, Luís B.; Cyrino, Edilson S. (Wiley-Blackwell, 2015)
To analyze the relationship between different physical activity (PA) domains and sociodemographic, psychological, behavioral and biological factors in Brazilian adolescents. 1,220 adolescents (55.1% female) aged between 10 and 16 years-old participated in this study. The Baecke questionnaire was used to evaluate different PA domains, namely occupational, sports and leisure-time. Socioeconomic status, number of siblings, friendships satisfaction, mother's and father's PA level and previous experience with sports were self-reported. Cardiorespiratory fitness, waist circumference, and somatic maturity were estimated by objective indicators. Linear regression was used for the main statistical analysis. The variables consistently related to all of the PA domains were gender (boys more active), friendship satisfaction (positive with sports and leisure-time PA and negative with occupational PA) and cardiorespiratory fitness (positive). There were also domain-specific relationships for occupational (number of siblings [β = 0.02] and father's PA [β = 0.13]), sport practice (previous experience with sports [β = 0.33], waist circumference [β = 0.01] and somatic maturity [β = -0.12]) and leisure-time PA (chronological age [β = -0.15], mother's PA [β = 0.47] and previous experience with sports [β = 0.17]). The different domains of PA are related to specific variables in adolescence. This information may be helpful in formulating strategies for physical activity promotion, particularly in adolescents from low-to-middle income countries.